Seed oil from Harmal (Rhazya stricta Decne) grown in Riyadh (Saudi Arabia): a potential source of δ-tocopherol - Nehdi, Imededdine Arbi; Mohamed Sbihi, Hassen; Tan, Chin Ping; Al-Resayes, Saud Ibrahim (Elsevier BV, 2016)
Rhazya stricta (R. stricta) known as Harmal is widely distributed in Saudi Arabia and throughout the Middle East. It is used as a medicinal plant in traditional cultures and the seeds are a source of unsaturated oil. In the present study, tocol (tocopherol and tocotrienol), triacylglycerol, and fatty acid compositions, pigment content, thermal behavior, and various physicochemical properties of R. stricta oil were characterized to determine the potential uses of this seed oil. Our results indicate that the oil is a rich source of bioactive molecules, including δ-tocopherol (896 mg/100 g), γ-tocopherol (148 mg/100 g) and carotenoids (15.67 mg/kg). The oil content of the seeds was 13.68% and the triacylglycerols mainly consisted of linoleic acid (59.03%), and oleic acid (27.01%). The major triacylglycerols were trilinoleate, dilinoleate and monolinoleate. The ratio of unsaturated to saturated fatty acids (UFA/SFA) in the oil was high (9.20). Additionally, the oil showed a high degree of thermal stability and a low melting point of approximately −25 °C. These data indicate that R. stricta seed oil, which is low in saturated fats and rich in bioactive compounds, is potentially useful in food and pharmaceutical applications.